Delayed presentation of pericardio-diaphragmatic hernia following blunt trauma: A case report. (December 2019) - Reid, Jennifer E.; Gupta, Shailvi; Scalea, Thomas M.; Stein, Deborah M.
Abstract: Pericardio-diaphragmatic hernias (PDHs) are exceedingly rare. When found in adults, they are most commonly caused by blunt trauma and require immediate repair. We report a case of a 61-year-old female who presented with shortness of breath, chest pain and fatigue one month after a motor vehicle collision. Imaging revealed an anterior diaphragmatic rupture with herniation of transverse colon and omentum into the left hemithorax with mass effect on the anterior heart. She underwent exploratory laparotomy revealing a pericardio-diaphragmatic hernia with contents further herniating through a lateral pericardial defect into the left chest. The pericardio-diaphragmatic defect was repaired primarily with non-absorbable sutures. There is an average of only one case report of PDH annually and to our knowledge, this is the first report of pericardio-diaphragmatic hernia with concomitant lateral pericardial defect with herniation of contents into the chest.